2017
DOI: 10.1590/1807-3107bor-2017.vol31.0075
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signaling 1 expression during LPS-induced inflammation and bone loss in rats

Abstract: This study aimed to characterize the dynamics of suppressor of cytokine signaling (SOCS1) expression in a rat model of lipopolysaccharideinduced periodontitis. Wistar rats in the experimental groups were injected three times/week with LPS from Escherichia coli on the palatal aspect of the first molars, and control animals were injected with vehicle (phosphate-buffered saline).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…On the other hand, gingival crevicular fluid levels of IL-6 and IFN-γ have been found to be remarkably higher in these patients compared with healthy controls [ 20 ]. Another study has detected parallel up-regulation of SOCS1 and IFN-γ in the experimental model of periodontitis [ 8 ]. These findings indicate the presence of a complicated network between cytokines, their regulatory factors and their mediators in the context of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, gingival crevicular fluid levels of IL-6 and IFN-γ have been found to be remarkably higher in these patients compared with healthy controls [ 20 ]. Another study has detected parallel up-regulation of SOCS1 and IFN-γ in the experimental model of periodontitis [ 8 ]. These findings indicate the presence of a complicated network between cytokines, their regulatory factors and their mediators in the context of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have indicated the role of SOCS proteins in this disorder. For instance, expression of SOCS1 has been found to be increased in the experimental model of periodontitis, parallel with activation of STAT1 and NF-κB pathways [ 8 ]. Moreover, down-regulation of SOCS3 in myeloid cells has resulted in enhancement of Porphyromonas gingivalis -induced inflammatory responses and over-production of interleukins-1β, -6, and -8 by peritoneal macrophages [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… There is relationship between suppressor of cytokine signaling 1 expression, during LPS‐induced inflammation, and bone loss in rats (Souza et al., ). CCR5Δ32 (rs333) polymorphism is associated with decreased risk of chronic and aggressive periodontitis (Cavalla et al., ). Patients carrying haplotypes associated with susceptibility to chronic periodontitis can modify absolute quantification of Aggregatibacter actinomycetemcomitans (Cirelli et al., ). Genome‐wide association scan for chronic periodontitis implicates novel locus for periodontitis covariants (Feng et al., ). …”
Section: Periodontitis and Peri‐implant Diseasesmentioning
confidence: 99%
“…1. There is relationship between suppressor of cytokine signaling 1 expression, during LPS-induced inflammation, and bone loss in rats (Souza et al, 2017). 2.…”
Section: Brazil Contextualizationmentioning
confidence: 99%